2021
DOI: 10.1155/2021/6630404
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge, Attitudes, and Practice in Relation to Pharmacovigilance and Adverse Drug Reaction Reporting: A Systematic Review

Abstract: Aim. To describe and synthesize aspects of knowledge, attitudes, and practice regarding pharmacovigilance and adverse drug reaction (ADR) reporting and to explore associated barriers from a nurse perspective. Methods. A systematic review was conducted. Electronic databases including MEDLINE, Embase, Scopus, and Web of Knowledge from January 2010 to October 2020 were searched. Original observational studies that were written in English and which focused on nurses’ knowledge, attitudes, practice, and perceived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 73 publications
3
10
2
Order By: Relevance
“…According to our review findings, healthcare professionals’ competencies for PRN medicines management influenced the safety of the medication process. Their pharmacological competence as having sufficient knowledge and skills to manage real-life medication circumstances and making appropriate decisions ( Sulosaari et al, 2011 ; Salehi et al, 2021 ) are affected by the complexity of the patient’s medication processes ( Sulosaari et al, 2011 ; Lichtner et al, 2016 ). Healthcare providers need education and training about the application of alternative and non-pharmacological interventions for relieving patients’ symptoms ( Molloy et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our review findings, healthcare professionals’ competencies for PRN medicines management influenced the safety of the medication process. Their pharmacological competence as having sufficient knowledge and skills to manage real-life medication circumstances and making appropriate decisions ( Sulosaari et al, 2011 ; Salehi et al, 2021 ) are affected by the complexity of the patient’s medication processes ( Sulosaari et al, 2011 ; Lichtner et al, 2016 ). Healthcare providers need education and training about the application of alternative and non-pharmacological interventions for relieving patients’ symptoms ( Molloy et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of confidence in discussing a suspected ADR with other colleagues is another major barrier. The studies have identified that a lack of confidence in determining whether a drug has caused an ADR or otherwise could also be a determinant of underreporting [27,[43][44][45]. A study by Gupta et al (2018) showed that 7.5% of participants including pharmacists and nurses identified a lack of confidence to report an ADR as a barrier [46].…”
Section: Plos Onementioning
confidence: 99%
“…As Iffat et al (2014), Nisa et al (2018) and Syed et al (2018) indicated that HCPs had poor knowledge about ADR reporting systems and the unavailability of incentives, and a professional environment hindered the ADR reporting [21][22][23]. Previous studies have documented that awareness about the PV system, education and training can improve the ADR reporting among HCPs [23][24][25][26][27]. A recent study has analyzed the core indicators responsible for a functional PV system in Pakistan [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such demands require teamwork, and while the importance of interprofessional collaboration is widely acknowledged, most commonly it is the doctor–pharmacist partnership that is described in the literature [ 24 ]. The nursing contribution to prevention and management of ADRs has traditionally focused on preventing medication administration errors [ 25 , 26 , 27 ], with nurse monitoring for adverse effects of medicines often being an aspiration, rather than reality [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses’ ability to detect adverse drug reactions may be limited by lack of clarity regarding their role [ 29 ] or the extent of their pharmacological knowledge [ 27 , 30 ], and a comprehensive tool that does not require extensive specialist expertise could facilitate such monitoring. The ADRe Profile [ 31 ] is a structured nurse-led intervention designed to help health care professionals detect adverse side effects and adverse events related to patients’ primary care medicines and to review general health and well-being, in case this has worsened as a result of prescribed medicines.…”
Section: Introductionmentioning
confidence: 99%